Motor synergies research in physical therapy: advantages of the uncontrolled manifold approach - Daniela Virgínia Vaz (Universidade de São Paulo, 2017)
ABSTRACT Movement is central to physical therapy identity and practice. Advances in the science of movement control, motor learning and development are thus inextricably tied to professional development and clinical activity. This paper aims to describe a prominent approach to motor control with potential to greatly advance the understanding of movement dysfunction: the uncontrolled manifold (UCM). An argument is formulated for incorporating this method of data analysis in rehabilitation research. It is a narrative review of the relevant literature. Research in physical therapy could greatly benefit from investigating synergies with the theory and methods of UCM. Research should seek connections between functioning in daily life tasks and the assembling of synergies to stabilize different performance variables, the UCM variability measures, the synergy strength indexes, and the anticipatory synergy adjustments. Changes in these synergy variables should also be quantified after rehabilitation interventions. UCM can offer one solid science-based approach to inform clinical decisions on whether synergies have to be broken, rebalanced, created, or reinforced in patients with movement dysfunction.